Effect of Marketing Strategy and Service Quality on Product Purchasing Decisions - Widiyanto, Nugroho Eko; Pono, Maat; Alamszah, Nur (International Journal of Multidisciplinary Approach Research and Science, 2023)
The purpose of this study was to determine the effect of marketing strategy and service quality on product purchasing decisions. This research was conducted on one of the skincare sales brands, Feryal Skincare. The number of samples taken was 103 feryal skincare users with the criteria of (a) Users in the city of Makassar, (b) focusing on users in 2022 and 2023, (c) using feryal skincare products more than 1 time. Data collection was carried out through questionnaires and interviews. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis it is known that marketing strategy has a positive and significant effect on purchasing decisions, and service quality has a positive and significant effect on purchasing decisions